2003
DOI: 10.1002/er.894
|View full text |Cite
|
Sign up to set email alerts
|

Performance study of a partial gasification pressurized combustion topping gas cycle and split rankine combined cycle: Part I? Energy analysis

Abstract: SUMMARYThe aim of this paper is to study the thermodynamic performance of a new combination of a partial gasification pressurized combustion topping gas cycle and a split Rankine bottoming steam cycle as a means of advanced clean coal power generation. Energy analysis of the conceptualized power cycle is presented in this part of the paper. The effects of design and operating parameters of both the gas and the steam cycles on the performance of the power cycle are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Biba et al [8] Yoon et al [13] Amundson and Arri [16] Bhattacharya et al [6] Caram and Fuentes [27] Adanez and Labiano [28] Present work…”
Section: Parametersmentioning
confidence: 93%
See 2 more Smart Citations
“…Biba et al [8] Yoon et al [13] Amundson and Arri [16] Bhattacharya et al [6] Caram and Fuentes [27] Adanez and Labiano [28] Present work…”
Section: Parametersmentioning
confidence: 93%
“…Radial transport and radial temperature gradient were also neglected in that model. De et al [8] studied the effect of design and operating parameter of both gas and steam cycle on the performance of partial gasification, pressured combustion combined power plant using first law. They reported that the efficiency of combined cycle increases significantly with higher pressure ratio.…”
Section: 41mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is the same range as in the current study. De et al [21] used specific parameters. The enthalpy values for the steam cycle at each state are within the operating range when compared with an existing power plant [22].…”
Section: Validation Of Resultsmentioning
confidence: 99%
“…In the present work, a novel combined cogeneration cycle employing coal gasification in a topping clean coal technology based gas turbine cycle and a bottoming multipressure 'split Rankine' [4] cogeneration cycle has been conceptualized. The idea of generating steam in a heat recovery steam generator (HRSG) at different pressures for use in power generation has already been discussed from the energy and exergy viewpoints in an 'internally coupled' [4] combined power cycle by De et al [17,18] and in an 'externally coupled' [4] cogeneration plant by De and Biswal [19]. It has been found that the performance, both energetically and exergetically, is better for an externally coupled cycle and cogeneration than for an internally coupled cycle and power only option.…”
Section: Introductionmentioning
confidence: 99%